Geochemistry of Mercedes-Peatland (PAT18-MP) peat core from Patagonia - Michael S Bunsen; Julie Loisel (PANGAEA, 2021)
Peatland core geochemistry and chronology data for site BP (Beef-Penguin unofficially).